The Ambulatory and Home Care Record: A Methodological Framework for Economic Analyses in End-of-Life Care - Denise N. Guerriere; Peter C. Coyte (Journal of Aging Research)
Provision of end-of-life care in North America takes place across a multitude of settings, including hospitals, ambulatory clinics and home settings. As a result, family caregiving is characteristically a major component of care within the home. Accordingly, economic evaluation of the end-of-life care environment must devote equal consideration to resources provided by the public health system as well as privately financed resources, such as time and money provided by family caregivers. This paper addresses the methods used to measure end-of-life care costs. The existing empirical literature will be reviewed in order to assess care costs with areas neglected in this body of literature to be identified. The Ambulatory and Home Care Record, a framework and tool for comprehensively measuring costs related to the provision and receipt of end-of-life care across all health care settings, will be described and proposed. Finally, areas for future work will be identified, along with their potential contribution to this body of knowledge.